RP-HPLC Accelerated Degradation Method Development and Validation for Determination of Amlodipine and Atorvastatin in Combination Dosage Form of Tablet - Chabukswar, Anuruddha Rajaram; Sakpal, Pramod Hindurao (Indian Journal of Pharmaceutical Education and Research, 2021)
Aim: The Cost effective, Accurate, Precise Accelerated degradation method has been developed for determination of Atorvastatin and Amlodipine in combination dosage form of tablet and validated as directed by ICH guidelines. Objectives: To develop and validate analytical method which can be easily adoptable in frequent analysis of Amlodipine and Atorvastatin combinations in the laboratories. Materials and Methods: The 0.02 M potassium dihydrogen phosphate: acetonitrile: methanol (30:10:60 v/v/v) was used as mobile phase and pH 4 adjusted using ortho phosphoric acid at flow rate 1.0 ml/min. The column used for method development was Octadecylsilane-C18 (5 μm, 25 cm × 4.6mm, i. d.). The peaks obtained in the chromatogram were well resoluted. The scanning wavelength used was 244 nm with PDA detector. Results: The linearity for both the drugs was found between 05 - 30 μg/ml for both drugs with regression coefficient equation 0.995 and 0.999 at retention time 8.32 min and 11.09 min for Amlodipine and Atorvastatin respectively. The results obtained were statistically validated as directed by ICH guidelines and was found satisfactory. Conclusion: The developed and validated method was found to be very specific, accurate and precise. It can be utilized for routine analysis of combined dosage form of Amlodipine and Atorvastatin in the laboratory.
Keywords: Amlodipine; Atorvastatin; RP-HPLC; ICH Guidelines; PDA Detector; Validation